Preemptive parasternal intercostal nerve block for patients undergoing off-pump coronary artery bypass grafting: a double-blind, randomized, controlled trial - Zou, Mengmeng; Ruan, Wei; Liu, Jintao; Xu, Junmei (Frontiers in Cardiovascular Medicine, 2023)
Background: Parasternal intercostal nerve block has been increasingly used for postoperative analgesia and has shown that this technique can provide effective postoperative analgesia. This study aimed to investigate the effect of preemptive parasternal intercostal nerve block on the opioid and vasoactive drug dose required for intraoperative hemodynamic stability and postoperative analgesia in patients undergoing off-pump coronary artery bypass grafting. Methods: In this prospective, randomized controlled study, 64 participants aged 45–75 years scheduled for off-pump coronary artery bypass grafting at The Second Xiangya Hospital of Central South University. Patients were randomized into two groups and preoperatively administered ropivacaine (group R) and saline (group S), in the parasternal intercostal spaces with ultrasound-guided bilateral nerve block. Results: The primary outcome was intraoperative sufentanil and vasopressor dosage. The secondary outcomes were intraoperative hemodynamics, postoperative pain scores, and anesthesia recovery, postoperative use of rescue dezocine, stay in intensive care unit, and length of hospital stay. The consumption of intraoperative sufentanil and vasopressor was significantly lower in group R than in group S. The visual analog score in group R was significantly lower than that in group S up to 12 h postoperatively. The time to anesthesia recovery was significantly less in group R than in group S. Most patients in group S required rescue dezocine, whereas most patients in group R did not. The hemodynamic variables were stable in all patients. Conclusions: A preemptive parasternal intercostal nerve block effectively reduced the required intraoperative sufentanil and norepinephrine dose and provided adequate analgesia for the first 12 h after surgery. Therefore, a preemptive parasternal intercostal nerve block is a good option for patients undergoing off-pump coronary artery bypass grafting. Trial registration: This study was registered at chictr.org.cn (identifier: ChiCTR1800017210; registered July 18, 2018).